The role of FDG‐PET imaging as a prognostic marker of outcome in primary mediastinal B‐cell lymphoma. (10th September 2014) - Nagle, Sarah J.; Chong, Elise A.; Chekol, Seble; Shah, Nirav N.; Nasta, Sunita D.; Glatstein, Eli; Plastaras, John P.; Torigian, Drew A.; Schuster, Stephen J.; Svoboda, Jakub
Abstract Primary mediastinal B‐cell lymphoma (PMBL) is a subtype of diffuse large B‐cell lymphoma (DLBCL) that arises in the mediastinum from B‐cells of thymic origin. Optimal management of patients with PMBL remains controversial. The present study evaluates outcomes of 27 PMBL patients treated with R‐CHOP with or without radiation therapy (RT). It investigates the role of both interim and posttreatment fluorodeoxyglucose‐positron emission tomography (FDG‐PET) as prognostic markers of outcome. Additionally, it assesses postprogression therapies in the six patients who had progressive disease. At a median follow‐up of 41.5 months (range: 6.1–147.2 months), OS was 95.5% (95% CI = 71.9–99.4) and progression‐free survival (PFS) was 70.4% (95% CI = 49.4–83.9) for the entire cohort. The negative predictive values of interim and posttreatment FDG‐PET scans were both 100%. Patients who failed initial therapy and were treated with salvage regimens and autologous stem cell transplantation (ASCT) all achieved and maintained CR. PMBL patients can achieve excellent outcomes with minimal toxicities when treated with R‐CHOP with or without RT. Negative interim and negative posttreatment FDG‐PET results identified PMBL patients who achieve long‐term remission. However, the significance of both positive interim and positive posttreatment FDG‐PET results needs to be better defined. Those who failed initial therapy were successfully treated with salvage regimens and ASCT.